A Comparative Study on Water Productivity of Rice under Different Cultivation Practices - Das, D. M.; Mailapalli, D. R.; Dalai, A.; Kumar, N. (Journal of Agricultural Engineering, 2019)
Rice production in India needs to be increased to meet the future food demand of the ever- growing population and under the constraints of land, water, climate and other socio-environmental factors. Rice is the staple food in India, and needs maximum water among cereal crops. Improved rice cultivation practices (RCP) such as System of Rice Intensification (SRI), Alternate Wetting Drying (AWD), Bund Plugging (BP) and Raised Bed (RB) could potentially increase the water productivity over conventional (CON) rice cultivation practice. Field studies were conducted to estimate water productivity (WP) of these improved rice cultivation practices at Kharagpur during the kharif season of 2014 and 2015. Highest grain yield was recorded in SRI practice (5.57-5.60 t.ha-1) among all RCPs. Bund plugging practice showed the highest WP and statistically similar yield to SRI. Maximum irrigation water saving could be made with BP (44.8-60.1 %) among other RCPs, as compared to the conventional practice. It was concluded that BP is the best management practice with highest water productivity, irrigation water saving and commendable yield.